Teacher?s Professional Performance ? Prevailing Trends (Based on the Example of Teachers from the Małopolska Region in Poland) - Kosiba, Grażyna (INSTED: Interdisciplinary Studies in Education & Society, 2011)
The study aimed to show the structure of professional performance among the teachers of the Małopolska Region in Poland. It was attempted to find out what trends ? emancipation, subjective, heuristic and nonconformist, or rather objective, adaptive, stereotypical and conformist ? dominated in the educational activities and declarations of the teachers under the research. The research took place in the school year of 2004/2005, in the Małopolska region, Poland, and comprised 250 randomly chosen subjects, employed in different types of schools in Polish villages, towns and cities. To rate the standards of the teachers? role in their profession the PRN questionnaire (Rubacha 2000) had been used. The results of the study confirmed the prevalence of the adaptive and objective standard of the teachers? professional performance, saturated with conformist attitudes, and a lack of cohesion between the declarative and operative spheres in the subjects? everyday work situations.